2022
DOI: 10.3389/fmed.2022.964062
|View full text |Cite
|
Sign up to set email alerts
|

Toxic epidermal necrolysis in hepatitis A infection with acute-on-chronic liver failure: Case report and literature review

Abstract: Toxic epidermal necrolysis (TEN) and Stevens–Johnson syndrome (SJS) are acute inflammatory skin adverse reactions characterized by epidermal exfoliation and multi-site mucositis and are considered medical emergencies. The risk factors for SJS/TEN include immune disorders, malignancy, and genetic susceptibility. In most cases, medication is considered to be the leading cause of TEN. In addition, several studies suggest that infections, such as the herpes simplex virus, human immunodeficiency virus (HIV), Mycopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In 1989, Werblowsky-Constantini (39) first reported the case of a 35-year-old man with fever for 3 weeks, 50% skin lesions, hyperbilirubinemia, and high ALP levels, similar to our patient's liver function. Zang et al (40) also reported a case of TEN related to HAV infection in a 38-year-old male with cirrhosis and preexisting liver failure. The patient developed skin lesions 15 days after the TBIL reached its peak, accompanied by fever with a maximum body temperature of 39.0°C, and sustained remission was achieved with intravenous corticosteroids.…”
Section: Discussionmentioning
confidence: 96%
“…In 1989, Werblowsky-Constantini (39) first reported the case of a 35-year-old man with fever for 3 weeks, 50% skin lesions, hyperbilirubinemia, and high ALP levels, similar to our patient's liver function. Zang et al (40) also reported a case of TEN related to HAV infection in a 38-year-old male with cirrhosis and preexisting liver failure. The patient developed skin lesions 15 days after the TBIL reached its peak, accompanied by fever with a maximum body temperature of 39.0°C, and sustained remission was achieved with intravenous corticosteroids.…”
Section: Discussionmentioning
confidence: 96%
“…Stevens-Johnson syndrome/TEN is often triggered by medications but may also be secondary to infections such as pneumonia, herpes virus, and hepatitis [2]. It occurs at higher incidence in patients with human immunodeficiency virus and can have mimics such as in SJS-like acute graft-versus-host disease [3].…”
Section: Introductionmentioning
confidence: 99%
“…The mean adjusted mortality rates were 4.8% for SJS, 19.4% for SJS/TEN, and 14.8% for TEN [2]. Some of the identified causes of SJS/TEN include medications, mycoplasma pneumonia, herpes, hepatitis A, and vaccination [3]. The primary cause of this life-threatening disorder is drugs, with common examples being sulfonamides and anti-epileptic drugs such as phenytoin, carbamazepine, lamotrigine, phenobarbital, and allopurinol, as well as non-steroidal anti-inflammatory drugs like piroxicam, diclofenac, and nevirapine [4].…”
Section: Introductionmentioning
confidence: 99%